Combinatorially Designed Lipid‐like Nanoparticles for Intracellular Delivery of Cytotoxic Protein for Cancer Therapy1. (12th February 2014) - Wang, Ming; Alberti, Kyle; Sun, Shuo; Arellano, Carlos Luis; Xu, Qiaobing
Abstract An efficient and safe method to deliver active proteins into the cytosol of targeted cells is highly desirable to advance protein‐based therapeutics. A novel protein delivery platform has been created by combinatorial design of cationic lipid‐like materials (termed "lipidoids"), coupled with a reversible chemical protein engineering approach. Using ribonuclease A (RNase A) and saporin as two representative cytotoxic proteins, the combinatorial lipidoids efficiently deliver proteins into cancer cells and inhibit cell proliferation. A study of the structure–function relationship reveals that the electrostatic and hydrophobic interactions between the lipidoids and the protein play a vital role in the formation of protein–lipidoid nanocomplexes and intracellular delivery. A representative lipidoid (EC16‐1) protein nanoparticle formulation inhibits cell proliferation in vitro and suppresses tumor growth in a murine breast cancer model.